Trop-2 expression in non–small cell lung cancer - Peiwen Kuo; Emon Elboudwarej; Marianna Zavodovskaya; Kai-Wen Lin; Chingwei V. Lee; Lauri Diehl; Jilpa Patel; Sabeen Mekan; Juliane M. Jürgensmeier (PLoS ONE, 2025)
Trophoblast cell-surface antigen 2 (Trop-2) is highly expressed in non–small cell lung cancer (NSCLC) and has become an attractive target for antibody-drug conjugates (ADCs). ADC tumor target expression is essential in investigating the predictive value of Trop-2 and Trop-2 ADC efficacy. Although Trop-2 mRNA expression in NSCLC has been described, protein-level expression is poorly understood. We investigated Trop-2 expression landscape across multiple data and sample sets to characterize mRNA expression and address the gap in protein-expression profiling. Trop-2 expression was analyzed using available mRNA, mutation, and protein data in three datasets: (1) The Cancer Genome Atlas (TCGA) included clinical-pathological and survival data in NSCLC adenocarcinoma and squamous cell carcinoma; (2) sample set 1 (adenocarcinoma) and (3) sample set 2 (adenocarcinoma, squamous cell carcinoma) underwent sequencing and immunohistochemistry for Trop-2 RNA, protein (Robust Prototype Assay, SP295 clone) and mutation analysis. Trop-2 was highly expressed in NSCLC and expression was similar in adenocarcinoma and squamous cell carcinoma and across baseline characteristics including patient age, sex, and tumor stage. Trop-2 expression was not associated with clinically relevant genetic alterations. Trop-2 was not a prognostic factor in NSCLC (TCGA survival data). High Trop-2 expression in NSCLC was independent of evaluated baseline characteristics, histology, and driver alterations. Trop-2 protein expression at any level was observed in 82% to 90% of NSCLC across sample sets; similar proportions of adenocarcinoma and squamous cell carcinoma expressed Trop-2. These data support broad Trop-2 ADC use in NSCLC.